Risk Factors Associated with Surgical Site Infection in Pediatric Patients Undergoing Spinal Deformity Surgery: A Systematic Review and Meta-Analysis. Issue 3 (March 2020) - Matsumoto, Hiroko; Simhon, Matthew E.; Campbell, Megan L.; Vitale, Michael G.; Larson, Elaine L.
Abstract : Background: Considerable variation exists in surgical site infection (SSI) prevention practices for pediatric patients undergoing spinal deformity surgery, but the incidence of SSI has been reported to remain high in the United States. The literature reports various risk factors associated with SSI but findings are inconsistent. The purpose of this systematic review and meta-analysis was to assess the published literature investigating associations between various risk factors and SSI in pediatric patients undergoing spinal surgery. Methods: The systematic review and the meta-analysis were conducted according to Preferred Reporting Items for Systematic review and Meta-Analysis Protocols (PRISMA-P) guidelines among peer-reviewed journals published in English between January 2000 and April 2019. Studies that involved pediatric patients with spinal deformity undergoing surgical procedures in North America and assessed risk factors for SSI were included. The quality of individual studies was assessed, and weighted risk ratios and mean differences were calculated for each risk factor. Results: Of 763 potential articles identified, 13 met inclusion criteria; 7 studies were rated as average and 6, as poor quality based on the quality checklist. The meta-analysis demonstrated that the SSI risk increased by the following factors: 2.53 (95% confidence interval [CI], 1.26 to 5.10) for overweight to obese patients compared with patients with normal weight, 2.84 (95% CI, 1.67 to 4.81) for patients with a neuromuscular etiology compared with non-neuromuscular etiology, 1.69 (95% CI, 1.41 to 2.02) for patients with a gastrostomy tube (G-tube) compared with those without, 3.45 (95% CI, 2.08 to 5.72) for nonambulatory patients compared with ambulators, and 3.39 (95% CI, 2.38 to 4.83) for patients with pelvic instrumentation compared with those without. Patients who developed SSI also had 158.38 mL (95% CI, 46.78 to 269.97 mL) greater estimated blood loss compared with those who did not. Conclusions: Despite the limited quality of the available studies and wide variety of populations and outcome definitions, evidence suggests that overweight to obese status, neuromuscular etiology, use of a G-tube, nonambulatory status, instrumentation to the pelvis, and greater estimated blood loss are risk factors for SSI. The use of a common SSI definition and strong methodology are warranted for future studies. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete list of levels of evidence.